2021
DOI: 10.1016/j.sjbs.2020.11.074
|View full text |Cite
|
Sign up to set email alerts
|

Children Domestic Accidents Profile in Jazan Region, a call for new policies to improve safety of home environment

Abstract: High-frequency home accidents draw more attention to the protection of our home environment. WHO has reported that home deaths were among the first 20 causes of death in the 0–14 age group worldwide in 2012. This innovative research was designed to examine children under 15 years of age at home, in 2018 in the Jazan area of Saudi Arabia. Data were collected retrospectively from 19 hospitals in the Jazan area of southern Saudi Arabia during the period from September to December 2019. Data showed that, for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Supracondylar fractures (SCFs) are the most common elbow fracture in children [1][2][3]. Understanding the epidemiological characteristics and distribution of SCFs in different settings and countries is critical to implementing tailored prevention and treatment strategies such as raising awareness and focused health education programs on the causes of childhood accidents and home safety enhancement for parents and teachers in the Kingdom of Saudi Arabia, playground safety education and policy change in Korea and national action in China [4][5][6]. Several studies have evaluated the distribution of SCFs in many regions and countries and found that SCFs are more frequent in older children such as 55% (320/589, median age 7.4) reported by Landin et al and 58% (209/355, median age 7.9) reported by Houshian et al, and involve the nondominant, left side in most cases [3,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Supracondylar fractures (SCFs) are the most common elbow fracture in children [1][2][3]. Understanding the epidemiological characteristics and distribution of SCFs in different settings and countries is critical to implementing tailored prevention and treatment strategies such as raising awareness and focused health education programs on the causes of childhood accidents and home safety enhancement for parents and teachers in the Kingdom of Saudi Arabia, playground safety education and policy change in Korea and national action in China [4][5][6]. Several studies have evaluated the distribution of SCFs in many regions and countries and found that SCFs are more frequent in older children such as 55% (320/589, median age 7.4) reported by Landin et al and 58% (209/355, median age 7.9) reported by Houshian et al, and involve the nondominant, left side in most cases [3,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Common childhood injuries, such as road traffic injuries, burns, drowning, poisonings, and falls, occur frequently, with unintentional childhood falls being one of the most common injuries that happen to children and an important cause of childhood morbidity and mortality (1)(2)(3). Most pediatric fractures are associated with falls and frequently occur in the upper extremities due to their inclination to protect themselves with their arms during a fall (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Domestic scenarios, traditionally perceived as lower-risk environments, can unexpectedly harbor complex fractures, particularly when involving toddlers and young children [ 7 ]. Their exploratory nature and interaction with the household environment may contribute to unique injury patterns [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%